2014
DOI: 10.1155/2014/272481
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Autologous Chondrocyte Repair and Comparison to Other Cartilage Repair Techniques

Abstract: Articular cartilage defects have been addressed using microfracture, abrasion chondroplasty, or osteochondral grafting, but these strategies do not generate tissue that adequately recapitulates native cartilage. During the past 25 years, promising new strategies using assorted scaffolds and cell sources to induce chondrocyte expansion have emerged. We reviewed the evolution of autologous chondrocyte implantation and compared it to other cartilage repair techniques. Methods. We searched PubMed from 1949 to 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 75 publications
(78 reference statements)
1
96
1
3
Order By: Relevance
“…In contrast to our trial, a randomized controlled trial showed that first-generation ACI (n ¼ 58) was significantly better than mosaicplasty (n ¼ 42) after a mean follow-up of 19 months. 14 The proportion of patients with excellent or good results was 82% with ACI and 69% with mosaicplasty. We may hypothesized that the difference with our study is due to both differences in patients and assessments methods.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast to our trial, a randomized controlled trial showed that first-generation ACI (n ¼ 58) was significantly better than mosaicplasty (n ¼ 42) after a mean follow-up of 19 months. 14 The proportion of patients with excellent or good results was 82% with ACI and 69% with mosaicplasty. We may hypothesized that the difference with our study is due to both differences in patients and assessments methods.…”
Section: Discussionmentioning
confidence: 93%
“…Few studies have compared cartilage repair techniques. [12][13][14] Furthermore, wide variations in the assessment methods and patient populations hinder comparisons across studies. In contrast to our trial, a randomized controlled trial showed that first-generation ACI (n ¼ 58) was significantly better than mosaicplasty (n ¼ 42) after a mean follow-up of 19 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACI initial technique, where a periosteal flap is used to maintain the transplanted chondrocytes, is the only technique that is US FDA-approved [33]. While it has shown favorable results with 73.5% success at mean 12.8 years post surgery [34], remain the issue of 30% periosteum hypertrophy and a limitation to lesions small in size (average defect size 5.2 cm 2 ).…”
Section: Cell-based Productsmentioning
confidence: 99%
“…They consist of crosslinked hydrophilic polymer networks having the attractive feature of being minimal-invasively injected as a solution and capable to polymerize in situ. Crosslinking methods include light irradiation, temperature modulation and pH alteration [33]. Hydrogels used for chondrogenesis can be naturally-derived such as agarose [44,45], collagen [46,47], fibrin [48,49], alginate [50][51][52] and hyaluronan [53]; or derive from synthetic polymers such as polyethylene glycols hydrogels [54,55].…”
Section: Hydrogelsmentioning
confidence: 99%